What makes icons appealing? The role of processing fluency in predicting icon appeal in different task contexts. (July 2016) - McDougall, Siné; Reppa, Irene; Kulik, Jozef; Taylor, Alisdair
Abstract: Although icons appear on almost all interfaces, there is a paucity of research examining the determinants of icon appeal. The experiments reported here examined the icon characteristics determining appeal and the extent to which processing fluency – the subjective ease with which individuals process information – was used as a heuristic to guide appeal evaluations. Participants searched for, and identified, icons in displays. The initial appeal of icons was held constant while ease of processing was manipulated by systematically varying the complexity and familiarity of the icons presented and the type of task participants were asked to carry out. Processing fluency reliably influenced users' appeal ratings and appeared to be based on users' unconscious awareness of the ease with which they carried out experimental tasks. Highlights: Ease of processing is a heuristic determining preferences in a wide range of tasks. Ease of processing affected appeal evaluations for icons. Icons which were easier to find and identify were evaluated more positively. Appeal evaluations mirrored patterns of performance; both depend on processing ease. Ease of processing heuristics may explain relationships observed between usability and appeal.